2015
DOI: 10.1016/j.econmod.2014.10.044
|View full text |Cite
|
Sign up to set email alerts
|

Does gold act as a hedge or a safe haven for stocks? A smooth transition approach

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
194
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 339 publications
(231 citation statements)
references
References 59 publications
12
194
3
1
Order By: Relevance
“…This is in line with the reported literature (e.g. Baur and McDermott 2010, Ciner et al 2013, Mensi et al 2015, Bredin et al 2015, Beckmann et al 2015, Śmiech and Papież 2016, Raza et al 2016. However, the main exceptions are the extreme bearish conditions These findings suggest that gold provides hedging and diversification benefits to the major stock markets of the investment universe (e.g.…”
Section: Estimates Of the Qq Approachsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in line with the reported literature (e.g. Baur and McDermott 2010, Ciner et al 2013, Mensi et al 2015, Bredin et al 2015, Beckmann et al 2015, Śmiech and Papież 2016, Raza et al 2016. However, the main exceptions are the extreme bearish conditions These findings suggest that gold provides hedging and diversification benefits to the major stock markets of the investment universe (e.g.…”
Section: Estimates Of the Qq Approachsupporting
confidence: 92%
“…On other hand, beauty of gold is to love the bad news, and in response to adverse stock market movement its rising prices compensate the portfolio losses (Arouri et al 2015, Beckmann et al 2015, Śmiech and Papież 2016, Chkili 2016, Basher and Sadorsky 2016, Raza et al 2016. Also, compensate investors for many deterioration in purchasing power due to inflation or currency depreciation (Wang and Lee 2016, Aye et al 2016, Iqbal et al 2016.…”
Section: Related Literaturementioning
confidence: 99%
“…A number of existing studies have shown evidence of the hedging, diversifying and safe haven potential for stocks and bonds (e.g., Baur and McDermott, 2010;Baur and Lucey, 2010;Beckmann et al, 2015;Gürgün and Ünalmış, 2014;Bredin et al, 2015). For instance, Baur and McDermott (2010) investigate the role of gold in the global financial system with a focus on a sample of major developed and emerging markets (BRIC) and reported gold's safe-haven status with respect to stock market movements over the period 1979-2009, except for Australia, Canada and Japan.…”
Section: Introductionmentioning
confidence: 99%
“…(i) Baur and McDermott's (2010) paper, in which the analysis of daily, weekly and monthly rates of return in the period between 1979 and do 2009 lead to the conclusion that gold is a hedge and a safe haven for assets in European countries and in the USA, but is neither a hedge nor a safe haven for assets in developing countries and in Australia, Canada and Japan, (ii) Beckmann, Berger and Czudaj's (2015) paper, in which it is concluded, on the basis of the analysis of monthly rates of return in the period between 1970 and 2012, that: gold is a strong hedge for assets in the euro area, Indonesia, Russia and Turkey; gold is not a hedge for assets in China and Germany; gold is a hedge for assets in the remaining economies; gold is a strong safe haven for assets in India and Great Britain and is not a hedge in the euro area, Indonesia, and Russia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Joy (2011), Ciner, Gurdgiev andLucey (2013) use a DCC-GARCH model, while Reboredo (2013a), and Reboredo (2013b) use the copula function and dependencies in the tails of distribution to define the relations in turmoil. Beckmann, Berger and Czudaj (2015) use two-regime threshold model (smooth transition regression), in which one regime corresponds to normal market conditions, while the other to a market in crisis.…”
Section: Literature Reviewmentioning
confidence: 99%